Shape of the glucose response curve during an oral glucose tolerance test is associated with insulin clearance and muscle insulin sensitivity in healthy non‐obese men. Issue 4 (1st March 2020) - Kaga, Hideyoshi; Tamura, Yoshifumi; Takeno, Kageumi; Kakehi, Saori; Someya, Yuki; Funayama, Takashi; Furukawa, Yasuhiko; Suzuki, Ruriko; Sugimoto, Daisuke; Kadowaki, Satoshi; Nishitani‐Yokoyama, Miho; Shimada, Kazunori; et al.
Abstract: Individuals with a monophasic glucose response curve (GRC) during a 75‐g oral glucose tolerance test have a higher risk for type 2 diabetes than those with a biphasic GRC. However, no studies have addressed the association between GRC type and insulin clearance. Thus, we studied 49 healthy non‐obese Japanese men. We divided study participants into the monophasic or biphasic group based on the shape of their GRC. We evaluated tissue‐specific insulin sensitivity and insulin clearance using a two‐step hyperinsulinemic‐euglycemic clamp. The monophasic group had more visceral fat, lower insulin clearance and lower muscle insulin sensitivity than the biphasic group, whereas liver and adipose tissue insulin sensitivity, and insulin secretion were comparable. In conclusion, healthy non‐obese men with a monophasic GRC have lower insulin clearance and muscle insulin sensitivity. Abstract : A monophasic glucose response curve during 75‐g oral glucose tolerance test in apparently healthy non‐obese men is associated with reduced insulin clearance, lower muscle insulin sensitivity and more visceral fat accumulation compared with a biphasic curve.